2011
DOI: 10.1186/1746-4811-7-25
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of plant viral suppressor silencing activity in intact leaf lamina by quantitative fluorescent imaging

Abstract: BackgroundTransient expression of proteins in plants has become a favoured method over the production of stably transformed plants because, in addition to enabling high protein yields, it is both fast and easy to apply. An enhancement of transient protein expression can be achieved by plant virus-encoded RNA silencing suppressor proteins. Since viral suppressor proteins differ in their efficiency to enhance transient protein expression in plants, we developed a whole-leaf green fluorescent protein (GFP)-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Owing to their stability and ease of quantification, fluorescent protein‐based detection methods have garnered wide acceptance in plant studies. They can be imaged as well as quantified accurately from intact leaf tissues without any need for cell lysis or sample preparation (Dhillon et al ., ; Richards et al ., ; Stephan et al ., ). The expression of fluorescent proteins from viral genomes within the host cell can accurately reflect the viral gene expression level.…”
Section: Resultsmentioning
confidence: 97%
“…Owing to their stability and ease of quantification, fluorescent protein‐based detection methods have garnered wide acceptance in plant studies. They can be imaged as well as quantified accurately from intact leaf tissues without any need for cell lysis or sample preparation (Dhillon et al ., ; Richards et al ., ; Stephan et al ., ). The expression of fluorescent proteins from viral genomes within the host cell can accurately reflect the viral gene expression level.…”
Section: Resultsmentioning
confidence: 97%
“…The agroinfiltrated leaves were illuminated under a long-wavelength UV lamp (Black Ray model B 100 AP) and photographed at 4 days post-agroinfiltration (DPA). The GFP signal intensity was detected and measured by using an IVIS Lumina III LT in vivo Imaging System (XENOGEN Co., Alameda, CA, USA) [ 46 ]. All experiments were repeated three times.…”
Section: Methodsmentioning
confidence: 99%
“…Because of high variability in GFP fluorescence intensity between leaves, the levels of GFP expression were always compared separately between infiltrated patches in each leaf. At 5 dpi, GFP fluorescence was quantified and analysed using IVIS Lumina II (Caliper Life Sciences, Waltham, MA, USA) and Living Image (version 4.1) software as described in Stephan et al (2011) including the modifications reported in KĂ€rblane et al (2015). For the local silencing suppression assay, we measured radiant efficiency of GFP in agroinfiltrated leaves and analysed the difference between two patches in the same leaf using a paired two‐tail t ‐test.…”
Section: Methodsmentioning
confidence: 99%